2018
DOI: 10.1101/368829
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recurrent pregnancy loss is associated with a pro-senescent decidual response during the peri-implantation window

Abstract: SummaryThe fate of the human endometrium is determined during the mid-luteal window of implantation, coinciding with differentiation of endometrial stromal cells (EnSCs) into specialized decidual cells.In response to successful embryo implantation, differentiating EnSCs transform the endometrium into a decidua that maintains the placenta throughout gestation; whereas falling progesterone levels in the absence of pregnancy lead to tissue destruction and menstrual shedding. We used single-cell

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
141
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 43 publications
(145 citation statements)
references
References 77 publications
2
141
0
2
Order By: Relevance
“…Explorative investigations indicated that the increase in eMSC in response to sitagliptin is biologically meaningful and associated with a significant reduction in senescent decidual cells. This conclusion is based on expression analysis of DIO2 and SCARA5, which are marker genes of decidual cells and senescent decidual cells, respectively [26]. DIO2 encodes iodothyronine deiodinase 2, which catalyses the conversion of prohormone thyroxine (T4) into bioactive triiodothyronine (T3).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Explorative investigations indicated that the increase in eMSC in response to sitagliptin is biologically meaningful and associated with a significant reduction in senescent decidual cells. This conclusion is based on expression analysis of DIO2 and SCARA5, which are marker genes of decidual cells and senescent decidual cells, respectively [26]. DIO2 encodes iodothyronine deiodinase 2, which catalyses the conversion of prohormone thyroxine (T4) into bioactive triiodothyronine (T3).…”
Section: Discussionmentioning
confidence: 99%
“…However, these marker genes do not discriminate between decidual cells and senescent decidual cells [26]. By contrast, SCARA5 and DIO2 are marker genes of decidual cells and senescent decidual cells, respectively, both in vitro and in vivo [26]. PRL and IGFBP1 transcript levels were not significantly different in the second biopsy compared to the baseline biopsy in either the placebo or treatment group (Suppl.…”
Section: Explorative Investigations: Oral Sitagliptin Inhibits Decidumentioning
confidence: 97%
See 3 more Smart Citations